Characterization of Novel PI3Kδ Inhibitors as Potential Therapeutics for SLE and Lupus Nephritis in Pre-Clinical Studies - Haselmayer, Philipp; Camps, Montserrat; Muzerelle, Mathilde; El Bawab, Samer; Waltzinger, Caroline; Bruns, Lisa; Abla, Nada; Polokoff, Mark A.; Jond-Necand, Carole; Gaudet, Marilène; Benoit, Audrey; Bertschy Meier, Dominique; et al. (Frontiers in Immunology, 2014)
SLE is a complex autoimmune inflammatory disease characterized by pathogenic autoantibody production as a consequence of uncontrolled T-B cell activity and immune complex deposition in various organs, including kidney, leading to tissue damage and function loss. There is a high unmet need for better treatment options other than corticosteroids and immunosuppressants. Phosphoinositol-3 kinase δ (PI3Kδ) is a promising target in this respect as it is essential in mediating B- and T cell function in mouse and human. We report the identification of selective PI3Kδ inhibitors that blocked B-, T-, and plasmacytoid dendritic cell activities in human peripheral blood and in primary cell co-cultures (BioMAP®) without detecting signs of undesired toxicity. In an IFNα-accelerated mouse SLE model, our PI3Kδ inhibitors blocked nephritis development, whether administered at the onset of autoantibody appearance or the onset of proteinuria. Disease amelioration correlated with normalized immune cell numbers in the spleen, reduced immune complex deposition as well as reduced inflammation, fibrosis and tissue damage in the kidney. Improvements were similar to those achieved with a frequently prescribed drug for lupus nephritis, the potent immunosuppressant Mycophenolate mofetil (MMF). Finally, we established a pharmacodynamics/pharmacokinetic/efficacy model that revealed that a sustained PI3Kδ inhibition of 50% is sufficient to achieve full efficacy in our disease model. These data demonstrate the therapeutic potential of PI3Kδ inhibitors in SLE and lupus nephritis.